2018
DOI: 10.7150/thno.22012
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repurposing Screening Identifies Tioconazole as an ATG4 Inhibitor that Suppresses Autophagy and Sensitizes Cancer Cells to Chemotherapy

Abstract: Background: Tumor cells require proficient autophagy to meet high metabolic demands and resist chemotherapy, which suggests that reducing autophagic flux might be an attractive route for cancer therapy. However, this theory in clinical cancer research remains controversial due to the limited number of drugs that specifically inhibit autophagy-related (ATG) proteins.Methods: We screened FDA-approved drugs using a novel platform that integrates computational docking and simulations as well as biochemical and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
127
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 48 publications
1
127
0
Order By: Relevance
“…*p < 0.05, **p < 0.01, ***p < 0.001, NS: not significant proliferation of primarily cultured glioblastoma cells from patients (Additional file 3: Figure S3). A large body of evidence suggests that inhibition of the activity of other ATG4 family members, including ATG4A, ATG4B and ATG4D, could suppress tumor progression and enhance chemosensitivity or the efficacy of radiotherapy [42][43][44][45][46][47][48][49]. These findings consistently implied that the ATG4 family played an important role in tumorigenesis and cancer therapy.…”
Section: Discussionmentioning
confidence: 94%
“…*p < 0.05, **p < 0.01, ***p < 0.001, NS: not significant proliferation of primarily cultured glioblastoma cells from patients (Additional file 3: Figure S3). A large body of evidence suggests that inhibition of the activity of other ATG4 family members, including ATG4A, ATG4B and ATG4D, could suppress tumor progression and enhance chemosensitivity or the efficacy of radiotherapy [42][43][44][45][46][47][48][49]. These findings consistently implied that the ATG4 family played an important role in tumorigenesis and cancer therapy.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, clinical trials showed that autophagy is unable to be completely inhibited by CQ in vivo. These warrant us that searching more potent autophagy inhibitors is critical for promoting an opportunity to apply the combination therapeutic strategy in clinical studies (Lalita Guntuku et al, 2019), especially agents that specifically inhibit autophagyrelated (ATG) proteins (Pei-Feng Liu1 et al, 2018).…”
Section: The Challenge and Development Of Targeting Cytoprotective Aumentioning
confidence: 99%
“…ATG4B expression was found elevated in colorectal cancer, and knockdown of ATG4B resulted in reduced cell cycle progression and inhibition of colorectal cancer cell lines [92]. Some ATG4B inhibitors identified to date have been tested in xenograft models of colorectal cancer cells, typically HCT-116 cells, and demonstrated a significant benefit in reducing tumour growth, in particular when combined with chemotherapeutic agents [93].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Another luciferase-based sensor utilises the complementation of a split luciferase that is flanking LC3. In this arrangement, the uncleaved LC3 displays high levels of luminescence that is lost when cleaved by ATG4B [93]. This assay has been used to validate ATG4B inhibitors in cells, but the dynamic range of this assay is limited due to a high background activity.…”
Section: Cell-based Assaysmentioning
confidence: 99%
See 1 more Smart Citation